Green Human Resource Management in Islamic Finance: A Systematic Review of Sustainability Strategies in Indonesia - Suherman, Usep Deden; Wirdyansyah, Danial Muhammad; Mighwar, Muhammad Al; Syaie, Akhmad Najibul Khairi (Economica: Jurnal Ekonomi Islam, 2025)
This study investigates the implementation of Green Human Resource Management (GHRM) within Indonesia’s Islamic finance industry through a systematic literature review of 375 academic publications from 2015 to 2024. Existing research has largely centered on conventional financial institutions, offering limited insight into GHRM’s role in the Islamic finance context. The review reveals that GHRM practices—such as green recruitment, sustainability training, and eco-friendly incentives—not only improve operational efficiency but also align with Maqasid al-Shariah objectives. FinTech integration further enhances green initiatives by increasing transparency and access in Islamic financial services. Nonetheless, regulatory limitations and inconsistent institutional support hinder broader adoption. A key recommendation is the introduction of Green Employee Sukuk: Shariah-compliant instruments issued by financial institutions to fund employee-led sustainability programs. Returns are tied to the performance of green investments, incentivizing employee engagement while reinforcing organizational environmental commitments. Strengthening regulatory frameworks and leveraging FinTech innovations are crucial for optimizing GHRM’s impact on sustainability in Indonesia’s Islamic finance sector.